Crisis and Crisis Management Practices in Small and Medium Sized Enterprises Based in the City of Gaziantep (Global Journal of Management and Business Research, 2014)
Enterprises with a growing obligation to sustain their business activities in economic environments of increased levels of uncertainty and risk as a result of the novel circumstances of a developing and changing world and the diverse influences thereof, must be in a position to assess these uncertainties and risks in an accurate manner and develop preparedness for potential crises. Contemporary studies point out that the fact that an enterprise faces a crisis is not necessarily as much of an issue as the type and the timing of that crisis and how prepared the organization is to tackle it. The most effective and decisive elements of crisis management are proper forecasting and the minimization of the adverse effects of a crisis through a timely application of appropriate preparedness measures. In this respect, this paper first presents a general theoretical framework for crises and crisis management, followed by a survey into the perception of crisis and crisis management held by small and medium s ized e nterprises a ctive a t t he G aziantep B aspınar industrial zone.
Keywords: crisis; crisis management; small and medium sized enterprises; SMEs